Attitude of patients with type 2 diabetes towards the disease versus chosen sociodemographic and medical factors – psychometric properties of the DAS-3 scale in the Polish version - Olszak, Cecylia; Nowicka, Elżbieta; Baczewska, Bożena; Łuczyk, Robert Jan; Kropornicka, Beata; Krzyżanowska, Ewa; Daniluk, Jadwiga (Journal of Education, Health and Sport, 2017)
Background: The objective of the study was to develop the initial assessment of psychometric properties in the Polish version of the Diabetes Attitude Scale (DAS-3P) for a group of people with type 2 diabetes and to determine the impact of the selected sociodemographic and medical factors on the patients’ attitude towards the disease. Materials and Methods: The study was conducted on a group of 227 people with type 2 diabetes who were treated at the Diabetes Outpatient Clinic and the Endocrinology Clinic of the Independent Public Clinical Hospital No 4 in Lublin. The theoretical accuracy was assessed by means of confirmatory and exploratory factor analysis and the method of scale DAS- 3 major axis. The accuracy of the DAS-3 scale was determined by examining the internal test congruity and analysing the value of Cronbach’s alpha coefficient. The differences between the mean valueswas determined by the t test and the single factor analysis of variance. Results: Following the revision, Cronbach’s alpha internal congruence coefficient reached a = 0.79 for the whole DAS-3P and the normality of the DAS-3P distribution does not deviate significantly from the symmetrical distribution. However,the study showed a statistically important difference (p < 0.05) between gender, place of residence, level of education, need for material support, participation in training and the mean DAS-3P score. The age, the presence of a domestic partner, job activity, BMI, duration of the disease, the treatment method, the concentration level of HbA1C were not of statistical importance (p > 0.05) for the DAS-3P scores. Conclusions: 1.There is a need to continue with the study into the psychometric properties of the DAS-3 scale in the Polish version on a large study population with type 2 diabetes, 2. The survey group of patients with type 2 diabetes shows a positive attitude towards their disease assessed by the DAS-3P, 3. Higher scores in the Diabetes Attitude Scale (DAS-3P) were obtained by males living in the city, with higher education background, in need of material support and participating in training on diabetes.